Recombinant Spider Silk: Promises and Bottlenecks - Ramezaniaghdam, Maryam; Nahdi, Nadia D.; Reski, Ralf (Frontiers in Bioengineering and Biotechnology, 2022)
Spider silk threads have exceptional mechanical properties such as toughness, elasticity and low density, which reach maximum values compared to other fibre materials. They are superior even compared to kevlar and steel. These extraordinary properties stem from long length and specific protein structures. Spider silk proteins can consist of more than 20,000 amino acids. Polypeptide stretches account for more than 90% of the whole protein, and these domains can be repeated more than a hundred times. Each repeat unit has a specific function resulting in the final properties of the silk. These properties make them attractive for innovative material development for medical or technical products as well as cosmetics. However, with livestock breeding of spiders it is not possible to reach high volumes of silk due to the cannibalistic behaviour of these animals. In order to obtain spider silk proteins (spidroins) on a large scale, recombinant production is attempted in various expression systems such as plants, bacteria, yeasts, insects, silkworms, mammalian cells and animals. For viable large-scale production, cost-effective and efficient production systems are needed. This review describes the different types of spider silk, their proteins and structures and discusses the production of these difficult-to-express proteins in different host organisms with an emphasis on plant systems.